A security-based survey and classification of cloud architectures, state of the art and future directions - Waqas, Ahmad; Muhammed Yusof, Zulkefli; Shah , Asadullah (IEEE, 2013)
This research paper aims to explore the underlying cloud computing architectures with respect to security and auditing services. As most of the standards have not been defined yet for cloud computing, academic and industrial researchers are participating with their ideas and proofs. We have surveys and classified the available cloud computing architectures into three categories which are 1) Architecture of Cloud Computing Security and Auditing, 2) Data Storage Security, privacy and Auditing of Data Leakage, and 3) Security and Auditing of Malicious Acts. This taxonomy and analysis of existing cloud architectures will be helpful to address the primary issues focusing the security and auditing perspectives in future research.